A Neutrosophic Approach to Evaluating Self-Perceived Professional Competency in Dentistry Students and Graduates - Frederick Zevallos-Velasquez; Yessika Madelaine Abarca Arias; Juvita Dina Soto Hilario; , Jairo Rafael Vidaurre Urrelo; Alejandro Chávez Paredes; Katia Medina-Calderon (Neutrosophic Sets and Systems)
This article addresses a key issue in dental education: how recent graduates and final-year students at the Faculty of Dentistry of the National University of San Marcos (UNMSM) perceive their readiness for professional practice. The study explores these self-assessments amid uncertainty, especially due to disruptions in clinical training during health restrictions. Traditional methods often overlook the ambiguity present in human perceptions during crises. To fill this gap, the study applies neutrosophic Z numbers, a method that captures degrees of certainty, indeterminacy, and contradiction in responses. Five competency dimensions were evaluated, revealing overall confidence in professional preparation but significant uncertainty in technical specialization and clinical management. Unlike conventional approaches, this method highlights subtle distinctions in perception and better reflects the complexity of training during times of disruption. The findings not only provide a deeper theoretical understanding of professional self-assessment in healthcare but also offer practical implications: the need to reinforce advanced clinical skills and management training. Thus, the study contributes both conceptually and methodologically, offering a nuanced tool for evaluating professional readiness in uncertain and evolving educational environments.